2006
DOI: 10.1167/iovs.05-1028
|View full text |Cite
|
Sign up to set email alerts
|

Increased Apoptosis and Abnormal Wound-Healing Responses in the HeterozygousPax6+/−Mouse Cornea

Abstract: The cumulative effect of abnormal wound-healing responses, characterized by increased stromal cell apoptosis and reduced levels of MMP-9 secretion may contribute to the corneal changes in the Pax6+/- mice. Possible contributions of elevated stromal cell apoptosis and other abnormal wound-healing responses to ARK are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…8,10 In experiments with Pax6 +/-mice, several insights have been gained into impaired corneal wound healing. 16,20 One important finding was that increased stromal apoptosis occurred after wounding, and it has been suggested that apoptosis, as well as deficient and delayed extracellular matrix metabolism, aggravated the corneal changes. 16 A summary of the corneal wound healing and stromal response in AAK is given in Table 1.…”
Section: B Oxidative Stress Wound Healing and Corneal Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…8,10 In experiments with Pax6 +/-mice, several insights have been gained into impaired corneal wound healing. 16,20 One important finding was that increased stromal apoptosis occurred after wounding, and it has been suggested that apoptosis, as well as deficient and delayed extracellular matrix metabolism, aggravated the corneal changes. 16 A summary of the corneal wound healing and stromal response in AAK is given in Table 1.…”
Section: B Oxidative Stress Wound Healing and Corneal Transparencymentioning
confidence: 99%
“…Increased oxidative stress present in AAK may lead to a greater extent of apoptosis in the corneal epithelium and abnormal corneal wound healing. 16 In these processes, peroxiredoxin 6, VEGF, gelsolin, apolipoprotein A-1, and zinc-α2 glycoprotein may play a substantial role. One study found elevated levels of dinucleotides Ap4A and Ap5A in aniridic tears.…”
Section: The Tear Filmmentioning
confidence: 99%
“…A volume of 3 ml of conditioned media from each sample was diluted 1 : 1 with deionised water, mixed with 6 ml of sample application buffer, and subjected to gelatin zymography as described by Ramaesh et al 14 For quantitative analysis, the gelatin zymograms were produced by loading further diluted conditioned media, containing only 1 ml of each sample. This was done to produce a clear non-overlapping band for each sample.…”
Section: Gelatin Zymography and Reverse Zymographymentioning
confidence: 99%
“…Apoptotic keratocytes may, however, be noted away from sites of epithelial injury in keratoconus corneas (Kim, et al, 1999), leading to the hypothesis that abnormally high levels of ongoing keratocyte apoptosis could play a role in the pathophysiology of this ectatic corneal disease (Kim, et al, 1999;Chwa, et al, 2006). Abnormally high levels of keratocyte apoptosis have also been associated with the pathophysiology of aniridia (Ramaesh, et al, 2006). Thus, it appears that stromal apoptosis is tightly controlled during homeostasis in the absence of corneal injury or disease.…”
Section: Introductionmentioning
confidence: 99%